The Least Nodal Disease Burden Defines the Minimum Number of Nodes Retrieved for Esophageal Squamous Cell Carcinoma - Zhang, Hanlu; Yan, Xiuji; Yang, Yu-Shang; Yang, Hong; Yuan, Yong; Tian, Dong; Li, Yin; Wu, Zhi-Yong; Wang, Yun; Fu, Jian-Hua; Chen, Long-Qi (Frontiers in Oncology, 2022)
Background Clinically, a single positive lymph node (SPLN) should indicate the least nodal disease burden in node-positive patients with esophageal squamous cell carcinoma (ESCC) and may also be used to define the minimum number of examined lymph nodes (NELNs) in ESCC patients. Methods Data from three Chinese cohorts of 2448 ESCC patients who underwent esophagectomy between 2008 and 2012 were retrospectively analyzed. Based on lymph node status, patients were divided into two groups: N0 ESCC and SPLN ESCC. A Cox proportional hazards regression model was used to determine the minimum NELNs retrieved to maximize survival for ESCC patients with localized lymph node involvement. The results were then validated externally in the SEER database. Results A total of 1866 patients were pathologically diagnosed with N0 ESCC, and 582 patients were diagnosed with SPLN ESCC. The overall survival rate of patients with N0 ESCC was significantly better than that of patients with SPLN ESCC (HR 1.88, 95% CI 1.64-2.13, P<0.001), but no significant difference was found between SPLN ESCC patients with ≥ 20 lymph nodes harvested and N0 ESCC patients (HR 1.20, 95% CI 0.95-1.52, P=0.13). Analysis of patients selected from the SEER database showed the same trend, and no significant difference was observed between N0 ESCC patients and SPLN ESCC patients with ≥ 20 lymph nodes retrieved (HR: 1.02, 95% CI 0.72-1.43, P=0.92). Conclusions A minimum of 20 lymph nodes retrieved should be introduced as a quality indicator for ESCC patients with localized lymph node involvement.